Legal and economic issues of improving the medical waste management system - Seilkassymova, R.A.; Nurmukhankyzy, D. (Bulletin of the Karaganda University “Law Series”, 2025)
Currently, the unfavorable environmental situation with medical waste in the Republic of Kazakhstan is one of the acute problems. In addition, nature and the population of Kazakhstan and neighboring countries are in a worse situation. In this article, the legal analysis of the improvement of the medical waste management system in the Republic of Kazakhstan is carried out, the legal foundations of the provision are considered. The analysis of the current state of medical waste management in a number of regions of the Republic of Kazakhstan has been carried out, the prerequisites for the application of an integrated approach to the disposal and neutralization of this type of waste within the framework of regional environmental policy have been studied. Based on the analysis of law enforcement practice, gaps in the legal regulation of the medical waste management system have been identified. A methodological approach is proposed, which is a feature of the legal and financial justification of the territorial schemes of medical waste management used in the regions. The methodological tools of the study include statistical methods of processing data on the disposal and disinfection of medical waste. The Republic of Kazakhstan is distinguished by increased attention to the methods of handling medical waste, the desire to ensure environmental safety and the prevention of violations of legislation in the disposal of medical waste. On the other hand, low satisfaction of the authorities was revealed with the pace of solving the problems of disposal of healthcare institutions not included in the process of medical activity, including medical waste requiring disinfection and recycling. The result of the study is proposals on the need for interregional cooperation in the field of placement and construction of complexes for the processing, disposal and neutralization of medical waste of various hazard classes. The authors propose as a promising direction of scientific and technological development to create a complex of high-tech equipment for the disposal of various types of medical waste with the production of secondary raw materials, as well as the neutralization of medical waste of increased and increased danger.